Cognitive Reappraisal in Children: Neuropsychological Evidence of Up-Regulating Positive Emotion From an ERP Study - Liu, Wen; Liu, Fang; Chen, Liang; Jiang, Zhongqing; Shang, Junchen (Frontiers in Psychology, 2019)
Emotion regulation is a critical mechanism in the socio-emotional development of children. Previous studies revealed that children use cognitive reappraisal to downregulate negative emotions. Moreover, the amplitude of late positive potential (LPP) shows a more obvious reduction following neutral interpretations than following negative interpretations. However, whether children can use cognitive reappraisal to regulate positive emotions remains unclear. In the present study, 46 eight- to twelve-year-old children were asked to reappraise the meaning of pleasant pictures. Electroencephalography (EEG) data were collected during the task. As predicted, LPP amplitudes increased more following reappraisal condition than following pleasant condition. The analysis of spatial-temporal shifting patterns showed that the effect occurred in the earlier window for the posterior region. As time progressed, this effect shifted toward the central and anterior regions. Taken together, the findings suggest that children can use cognitive reappraisal to upregulate positive emotions. [4589 words, three figures]